A Brief Review of Recent Research on Reversible Francis Pump Turbines in Pumped Storage Plants - Xiuli Mao; Jiaren Hu; Zhongyong Pan; Pengju Zhong; Ning Zhang (Energies)
As the core for energy conversion in pumped storage plants, the pump turbine is also a key component in the process of building a clean power grid, owing to its fast and accurate load regulation. This paper introduces the current status of research and development of pump turbines from the perspectives of significance, design and optimization, operational performance, advanced research methods, etc. Internal and external characteristics such as transient flow evolution, structural vibration, flow-induced noise, etc., not only reflect operational performance (hydraulic, cavitation, sediment abrasion, and stability performance, etc.) but also directly affect the safe and efficient operation of the system. It is worth mentioning that the space-time evolution of internal and external characteristics is an emerging research direction, the results of which can be used to predict the operational conditions of pump turbines. Moreover, the development and application of intelligent condition monitoring and fault diagnosis aim to prevent failures and accidents in pumped storage plants.